The Abrahamic faiths: Judaism, Christianity, and Islam - Dirks, Jerald F. (Amana Publications, 2004)
A Muslim in "atypical Christian" clothing -- The quest for Abraham : commonalities and contrasts among Judaism, Christianity, and Islam -- The Qurʼan, Ahadith, and Judaeo-Christian scriptures : finding common ground -- From Jesus to Muhammad : early Christianity and Islam -- Islam, the "people of the book," and religious pluralism - Islamophobia in the Christian West -- Original sin and the role of women : comparing the Abrahamic faiths -- Reconciliation and the children of Abraham